2016
DOI: 10.1111/wrr.12449
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin‐loaded keratin hydrogels reduce infection and support healing in a porcine partial‐thickness thermal burn

Abstract: Infection is a leading cause of morbidity and mortality in burn patients. Current therapies include silver-based creams and dressings, which display limited antimicrobial effectiveness and impair healing. The need exists for a topical, point-of-injury antibiotic treatment that provides sustained antimicrobial activity without impeding wound repair. Fitting this description are keratin-based hydrogels, which are fully biocompatible and support the slow-release of antibiotics. Here we develop a porcine model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 50 publications
(96 reference statements)
0
50
0
Order By: Relevance
“…Current research focuses on sustained delivery while maintaining bioactivity in order to reduce dressing changes, in turn reducing patient pain and burden on providers. Sustained delivery of antibiotics can be achieved by encapsulation into different hydrogel-based systems such as gelatin (Nunes et al, 2016 ), keratin (Roy et al, 2016 ), or chitosan (Hurler et al, 2012 ). Antibiotic incorporation into electrospun dressings (Chen et al, 2016 ; Dhand et al, 2016 , 2017 ) and occlusive dressings (Steinstraesser et al, 2011 ) has also shown superior activity and accelerated wound healing when compared to current clinical silver-based products.…”
Section: Inflammationmentioning
confidence: 99%
“…Current research focuses on sustained delivery while maintaining bioactivity in order to reduce dressing changes, in turn reducing patient pain and burden on providers. Sustained delivery of antibiotics can be achieved by encapsulation into different hydrogel-based systems such as gelatin (Nunes et al, 2016 ), keratin (Roy et al, 2016 ), or chitosan (Hurler et al, 2012 ). Antibiotic incorporation into electrospun dressings (Chen et al, 2016 ; Dhand et al, 2016 , 2017 ) and occlusive dressings (Steinstraesser et al, 2011 ) has also shown superior activity and accelerated wound healing when compared to current clinical silver-based products.…”
Section: Inflammationmentioning
confidence: 99%
“…Mice Third 92-95 10 10 × 10 mm 2 (Dai, Tegos et al, 2009) Rat Second or third 180 15 2 × 2 cm 2 (Shettigar, Jagannathan et al, 1982) Rat Second NR 10 1 × 1 cm 2 (de Almeida, Cardoso et al, 2013) Pig NR 90 20 5 × 5 cm 2 (Nunes, Rabelo et al, 2016) Mice Partial-thickness 70 (hot water) 4 15 × 15 mm 2 (Ito, Saito et al, 2015) Pig Third 100 30 5 × 5 cm 2 (Boucard, Viton et al, 2007) Rat Second 94 (hot water) 15 r = 1 cm (Alemdaroglu, Degim et al, 2006) NR Third 200 30 NR (Shen, Song et al, 2015) Pig Partial-thickness 100 22 d = 3 cm (Cylandeical) (Roy, Tomblyn et al, 2016) Rat Full-thickness 90 20 ф = 15 mm (circular) (Liu, Huang et al, 2017) Rat Full-thickness 85 20 d = 1.5 cm (rod) (Gupta, Upadhyay et al, 2013) Rat Full-thickness 85 15 NR (Heo, Yang et al, 2013) Rat Second 90 8 d = 3 cm (circular) (Meng, Chen et al, 2009) Rat Second 99 (water steam) 13 20 × 20 mm 2 (square) (Liu, Lin et al, 2012) Rat Second 90 10 2 × 3 cm 2 (Kossovich, Salkovskiy et al, 2010) Rat NR NR 10 250 mm 2 (MH, Saraswathi et al, 2010) NR Partial-thickness burn wound 80 10-12 min 300 mm 2 (Kumar, Khan et al, 2013) NR Full-thickness 100 8 NR (Abdullahi, Amini-Nik et al, 2014) Abbreviations: NR, not reported; R, radius; d, diameter; ф = area.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…The process of burn healing in mice is contraction, whereas in humans, it is granulation and re-epithelization (Wong et al, 2011;Abdullahi et al, 2014). The porcine model has emerged as a viable alternative to the mouse model particularly when studying wound healing as there is considerable similarity of skin structure, immune response, and healing pattern (re-epithelization) between pigs and humans (Abdullahi et al, 2014;Roy et al, 2016;Tsai D. M. et al, 2016). However, studies are limited to eight to nine experimental animals, due to high maintenance costs and strict ethical procedures, which limits statistical power and infection output kinetics.…”
Section: Introductionmentioning
confidence: 99%